ChemInform Abstract: Scope and Limitation for FeSO4‐Mediated Direct Arylation of Heteroarenes with Arylboronic Acids and Its Synthetic Applications. Issue 26 (1st July 2014) - Komeyama, Kimihiro; Nagao, Yuya; Abe, Manabu; Takaki, Ken
Abstract The FeSO4‐mediated direct arylation of heteroarenes with arylboronic acids in the presence of K2S2O8 is developed.